2022
DOI: 10.3390/molecules27092745
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability Enhancement of Cepharanthine via Pulmonary Administration in Rats and Its Therapeutic Potential for Pulmonary Fibrosis Associated with COVID-19 Infection

Abstract: Cepharanthine (CEP) has excellent anti-SARS-CoV-2 properties, indicating its favorable potential for COVID-19 treatment. However, its application is challenged by its poor dissolubility and oral bioavailability. The present study aimed to improve the bioavailability of CEP by optimizing its solubility and through a pulmonary delivery method, which improved its bioavailability by five times when compared to that through the oral delivery method (68.07% vs. 13.15%). An ultra-performance liquid chromatography tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…27 Finally, the sequencing data were aligned to the mouse reference genome (mm10) 28 . The read counts files were filtered with low expression and normalized by the ‘DEseq2’ package 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Finally, the sequencing data were aligned to the mouse reference genome (mm10) 28 . The read counts files were filtered with low expression and normalized by the ‘DEseq2’ package 22 …”
Section: Methodsmentioning
confidence: 99%
“…Asiaticoside (AS) is a triterpenoid saponin purified from the plant Centella asiatica with various biological effects, such as antioxidant, anti‐inflammatory and anti‐hepatofibric effects 18‐20 . Centella asiatica is a traditional Chinese medicine, which is widely used to wound healing and alleviating the symptoms of interstitial lung disease 21,22 . Tang et al found AS could inhibit the proliferation of fibroblasts and the expression of type I and type III collagen protein in the process of wound healing 23 .…”
Section: Introductionmentioning
confidence: 99%
“…CEP has been shown to have multiple molecular mechanisms, including stabilizing cell membrane fluidity ( Matsuda et al, 2014 ), inhibiting drug efflux ( Peng et al, 2012 ; Bailly, 2019 ), scavenging free radicals ( Rogosnitzky and Danks, 2011 ), alleviating inflammatory factor production, inhibiting cytoplasmic nuclear transcription factor (NF-κB) ( Lin et al, 2018 ) and activating the adenosine-activated protein kinase (AMPK) signaling pathway ( Fan et al, 2020 ), inhibiting the integrins/ILK/RACK1/PKCα/NF-κB signaling axis ( Yang et al, 2021 ), and inhibiting receptor activator of nuclear factor-κB (NF-κB) ligand (RANKL)-induced osteoclast formation and bone-resorbing activities ( Lin et al, 2018 ). These mechanisms have been linked to various biological activities of CEP, such as anti-inflammatory ( Bailly, 2019 ; Rogosnitzky et al, 2020 ), immunomodulatory ( Yamazaki et al, 2017 ; Bailly, 2019 ), anti-osteoporotic ( Zhou et al, 2018 ; Yao et al, 2022 ), antioxidant ( Bailly, 2019 ), inhibition of drug efflux transporters ( Peng et al, 2012 ; Kathawala et al, 2014 ), exerting protective effects against pulmonary fibrosis ( Li et al, 2022 ), anticancer ( Tang et al, 2018 ; Bailly, 2019 ; Rogosnitzky et al, 2020 ; Wang et al, 2020 ), and anti-parasitic effects ( Bailly, 2019 ). A historical overview of the research and development of CEP, which traces its main clinical applications and biochemical characteristics from 1934 to 2018, is presented in Figure 2 ( Bailly, 2019 ).…”
Section: A Brief Overview and Current Uses Of Cepmentioning
confidence: 99%
“…From a chemical perspective, CEP is also known as 12-O-methyl cepharanoline [ 24 ] and exhibits multiple pharmacological properties, including anti-inflammatory [ 25 ], immuno-regulatory [ 26 ], anticancer [ 27 ], and antiviral properties [ 28 , 29 , 30 ]. In a previous study, we found that CEP significantly reduced bleomycin (BLM)-induced collagen accumulation and inflammatory responses, engendering a protective effect against PF [ 31 ]. However, to the best of our knowledge, no studies have reported the underlying action mechanism of CEP in treatment against PF.…”
Section: Introductionmentioning
confidence: 99%